Accumulation by dispossession: A reflection on its introduction in Mozambique - Carlos de Matos, Elmer Agostinho; Vieira Medeiros, Rosa Maria (Universidade Federal Rural do Rio de Janeiro, 2015)
In the last times the accumulation by dispossession, materialized in the lands expropriation of poor populations and the privatization of public goods, characterize the actual form of accumulation of the capital. The present article intends to approach the implications of the introduction of the accumulation by dispossession in Mozambique, bringing by neoliberalism. Starting from four selected examples, we analyzed as the legal reforms facilitated the divestment of thousands of Mozambican families of their territories and forced to build a new history and identity in spaces without basic conditions for his survival.